IMPLEMENTING RELIGIOUS MODERATION THROUGH A CONTEXTUAL CURRICULUM AT RIYADLUS SHOLIHIN ISLAMIC ELEMENTARY SCHOOL, WONOASIH, PROBOLINGGO - Fredi, Mohammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Religious moderation is an important thing that must be present in every element of human life, including in every educational process. Because along with the ongoing process of human life, it will always be colored by social problems if it is not prevented with a character of loration through strengthening moderation, and until now, violence is still often found in the name of religion to discriminate against minority groups. This article aims to discuss the formulation of the concept of religious moderation in the context of Islamic perspective education. The hope is that it can be a reference in realizing the principle of moderation in education and as a study that supports the creation of moderation in Indonesia. The research method used is a literature study and its references are obtained from sources in the library or other media related to the discussion. The results of this study are the discovery of 4 aspects of moderation in amaliyah, namely Moderation in aqidah (Belief). Ubudiyah (Worship). Morals (Ethics). And Sharia (Tasyri'). In education, 4 discussions of religious moderation were found, namely first, in the subject matter, second, in the learning process, third, in learning assessment, fourth, in learning evaluation.